THE INFLUENCE OF GRAPE SEED DRYING TEMPERATURE ON THE QUALITY OF GRAPE SEED OIL - Ergović Ravančić, Maja (Journal on Processing and Energy in Agriculture, 2020)
As a by-product of the winemaking process, grape seeds have been receiving increased attention worldwide due to a number of beneficial nutritional properties. Moreover, grape seed oil has also been gaining prominence for its high content of unsaturated fatty acids, primarily linoleic acid (C18:2) (72-76%). The objective of this paper was to determine the influence of three different grape seed drying temperatures (20, 40 and 60 °C) on the quality of cold-pressed oils from five different grape varieties (Pinot noir, Pinot blanc, Muscat, Cabernet sauvignon and Graševina). The oils extracted were tested for the acid number (as an indicator of hydrolysis), the percentage of free fatty acids and the peroxide value (as an indicator of autoxidation). The peroxide values of the oil samples considered increased with the increasing drying temperature of grape seeds. The highest peroxide value was observed in the oil samples produced from the Graševina seeds (regardless of the grape seed drying temperature), whereas the Muscat oil samples exhibited the lowest peroxide values. The acid number and the percentage of free fatty acids of the oil samples considered were found to be variety specific and independent of the grape seed drying temperature.
Keywords: drying; grape; oil; grape seed